Mikrosistem Remaja yang Ketergantungan Obat - Gunawan, William (Noetic Psychology, 2012)
AbstrakIn Indonesian context, teenage drug addiction become a major issue that need further attention and intervention. This research was aimed to identify and and described the microsystem of drugs addiction in teenager. Using BronfrenbrennerÃ¢â¬â¢s ecology theory andÃÂ LeontyevÃ¢â¬â¢s activity system theory this research used a qualitative approach to describe the pattern and dynamic of three recovering teenager with drug addiction. The result showed that family aspect, school and peer pressure played an important factor in the microsystem of teenager with drug addict. There were also found that the same activity system occurred in the life of teenager with drug addict.ÃÂ ÃÂ Kata kunci : mikrosystem, activity system, teenager, drug addi